Survey On The Incidence And Severity Of Common Scab Of Potato In Bangladesh - Naher, Najmun; Hossain, Mohammad; Bashar, MA (Journal of the Asiatic Society of Bangladesh, Science, 2013)
A survey on the incidence and severity of common scab (Streptomyces sp.) of potato was made in the major potato growing districts of Bangladesh during the cropping season of 2007-2008. A total of 150 fields was surveyed for collection of potato common scab infected samples. It was observed that there was a lot of variation in disease severity and its incidence in different districts of Bangladesh. Highest per cent scab incidence (71.41 %) was recorded in Kahalo Upazila (Bogra) and lowest (13.79 %) in Pirgacha Upazila (Rangpur). Disease incidence also varied among the tested varieties namely, Cardinal, Diamant, Granola, Binella and Raja. Highest incidence was observed in Cardinal (54.08 %) followed by Binella (50.71 %) and it was lowest in Raja (3.07 %). Cardinal and Binella were found to be highly susceptible and Raja was resistant to common scab disease. Diamant, the commercial variety showed medium susceptible reaction to the disease. J. Asiat. Soc. Bangladesh, Sci. 39(1): 35-41, June 2013 DOI: http://dx.doi.org/10.3329/jasbs.v39i1.16031